Therapeutic Dilemma of Natural Watchman: Congenital Absence of the Left Atrial Appendage - Phoo Pwint Nandar; Asim Kichloo; Thein Tun Aung; Kevin D. Kravitz (Case Reports in Cardiology)
Congenital absence of the left atrial appendage is a rare congenital cardiac anomaly which is usually an incidental finding. We present a rare case of congenital absence of the left atrial appendage in a 77-year-old female patient with atrial fibrillation, and we will discuss the role of anticoagulation in the patient with congenital absence of the left atrial appendage based on the scientific data and theoretic background.